Mechanical drawing - French, Thomas Ewing (New York : McGraw-Hill, 1980)
A textbook introducing the basic theory, techniques, and uses of drafting for industrial arts and vocational high school students.
Includes index.
Keywords: Mechanical drawing; Mechanical drawing